Overcoming the blood–brain tumor barrier for effective glioblastoma treatment. (March 2015) - van Tellingen, O.; Yetkin-Arik, B.; de Gooijer, M.C.; Wesseling, P.; Wurdinger, T.; de Vries, H.E.
Abstract: Gliomas are the most common primary brain tumors. Particularly in adult patients, the vast majority of gliomas belongs to the heterogeneous group of diffuse gliomas, i.e . glial tumors characterized by diffuse infiltrative growth in the preexistent brain tissue. Unfortunately, glioblastoma, the most aggressive (WHO grade IV) diffuse glioma is also by far the most frequent one. After standard treatment, the 2-year overall survival of glioblastoma patients is approximately only 25%. Advanced knowledge in the molecular pathology underlying malignant transformation has offered new handles and better treatments for several cancer types. Unfortunately, glioblastoma multiforme (GBM) patients have not yet profited as although numerous experimental drugs have been tested in clinical trials, all failed miserably. This grim prognosis for GBM is at least partly due to the lack of successful drug delivery across the blood–brain tumor barrier (BBTB). The human brain comprises over 100 billion capillaries with a total length of 400 miles, a total surface area of 20 m 2 and a median inter-capillary distance of about 50 μm, making it the best perfused organ in the body. The BBTB encompasses existing and newly formed blood vessels that contribute to the delivery of nutrients and oxygen to the tumor and facilitate glioma cell migration to other parts of the brain. The high metabolic demands of high-grade glioma create hypoxic areas that trigger increased expression of VEGF and angiogenesis, leading to the formation of abnormal vessels and a dysfunctional BBTB. Even though the BBTB is considered 'leaky' in the core part of glioblastomas, in large parts of glioblastomas and, even more so, in lower grade diffuse gliomas the BBTB more closely resembles the intact blood–brain barrier (BBB) and prevents efficient passage of cancer therapeutics, including small molecules and antibodies. Thus, many drugs can still be blocked from reaching the many infiltrative glioblastoma cells that demonstrate 'within-organ-metastasis' away from the core part to brain areas displaying a more organized and less leaky BBTB. Hence, drug delivery in glioblastoma deserves explicit attention as otherwise new experimental therapies will continue to fail. In the current review we highlight different aspects of the BBTB in glioma patients and preclinical models and discuss the advantages and drawbacks of drug delivery approaches for the treatment of glioma patients. We provide an overview on methods to overcome the BBTB, including osmotic blood–brain barrier disruption (BBBD), bradykinin receptor-mediated BBTB opening, inhibition of multidrug efflux transporters, receptor-mediated transport systems and physiological circumvention of the BBTB. While our knowledge about the molecular biology of glioma cells is rapidly expanding and is, to some extent, already assisting us in the design of tumor-tailored therapeutics, we are still struggling to develop modalities to expose the entire tumor to such therapeutics at pharmacologically meaningful quantities. Therefore, we must expand our knowledge about the fundamentals of the BBTB as a step toward the design of practical and safe devices and approaches for enhanced drug delivery into the diseased brain area.